Medium-term immunogenicity of three doses of BNT162b2 and CoronaVac in Hong Kong neuromuscular disease patients - Michael Kwan Leung Yu; Sophelia Hoi Shan Chan; Daniel Leung; Samuel Cheng; Leo Chi Hang Tsang; Tsz Chun Kwan; Kaiyue Zhang; Xiwei Wang; Wenwei Tu; Malik Peiris; Yu Lung Lau; Jaime S. Rosa Duque (Human Vaccines & Immunotherapeutics)
The durability of the immunogenicity elicited by three doses of mRNA-based BNT162b2 and whole-virus inactivated CoronaVac in patients with neuromuscular diseases, particularly those on immunosuppressive drugs and variants of concern, has not been well-established. Our goal was to evaluate medium-term humoral immunogenicity outcomes after 3 doses of these vaccines. Peripheral blood samples were collected from participants 14–49 days and 155–210 days after administration of the third vaccine dose to assess humoral immune responses through serological assays. The immunogenicity outcomes of each patient were compared to those of three age-matched healthy control participants, ensuring a balanced comparison. Both patients that received 3 doses of BNT162b2 and 10 (90.9%) patients that received CoronaVac seroconverted against wild-type-SARS-CoV-2 virus, showing comparable antibody responses to healthy participants. After 6 months, one patient in BNT162b2 and all four patients in CoronaVac groups maintained seropositivity. The JN-1 specific binding antibody response was lower compared to wild-type virus. The use of corticosteroids did not affect seroconversion rate against wild-type virus or JN.1 variant. BNT162b2 and CoronaVac were immunogenic for neuromuscular diseases patients, maintaining durability after 6 months even for those on corticosteroids. Our data support a rapid immunization series utilizing mRNA-based and whole-virus inactivated vaccines for future pandemic.